Perancangan Arsitektur Enterprise untuk Sistem Peminjaman Ruang di Universitas Menggunakan FEAF - Naura Farica Rachman; Dika Priyanti; Fadhila Intan Cahyaningrum; Excel Ervinta Desty; Tarwoto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This research designs an Enterprise Architecture (EA) model for the space loan management system at Amikom Purwokerto University using the Federal Enterprise Architecture Framework (FEAF). The main objective is to improve efficiency, accuracy, and transparency in the space management process. The methodology used is descriptive qualitative approach with case study method. The research was conducted through the stages of problem identification, analysis of existing conditions, information architecture design, and classification of EA models. The main findings of the research show that the application of EA is able to speed up the process of borrowing space, reduce recording errors, and provide more accurate reports. The designed EA model includes four main perspectives: planning, ownership, design, and development. The contribution of this research is to provide an innovative and efficient solution for campus resource management through open-source technology.